2013
DOI: 10.1099/vir.0.052563-0
|View full text |Cite
|
Sign up to set email alerts
|

Natural infection of Atlantic salmon (Salmo salar L.) with salmonid alphavirus 3 generates numerous viral deletion mutants

Abstract: Salmon pancreas disease virus (SPDV) also referred to as salmonid alphavirus (SAV) is a virus causing pancreas disease in Atlantic salmon (Salmo salar L.) and rainbow trout (Oncorhynchus mykiss). Although the virus causes an economically important disease, relatively few full-length genome sequences of SAV strains are currently available. Here, we report full-length genome sequences of nine SAV3 strains from sites farming Atlantic salmon geographically spread along the Norwegian coastline. The virus genomes we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 46 publications
9
30
0
Order By: Relevance
“…Virus cultivation was unsuccessful, similar to earlier experiences with primary culture of SAV from infected fish (Christie et al 1998, López-Dóriga et al 2001, Graham et al 2003, Petterson et al 2013. Possible causes as low viral loads, virus neutralizing antibodies and/or defective virus particles in the samples have been suggested (Graham et al 2010, Petterson et al 2013. Challenges associated with primary isolation of SAV are also in accordance with our unpublished data from attempts to cultivate the virus from several outbreaks of PD in Norway.…”
supporting
confidence: 79%
See 1 more Smart Citation
“…Virus cultivation was unsuccessful, similar to earlier experiences with primary culture of SAV from infected fish (Christie et al 1998, López-Dóriga et al 2001, Graham et al 2003, Petterson et al 2013. Possible causes as low viral loads, virus neutralizing antibodies and/or defective virus particles in the samples have been suggested (Graham et al 2010, Petterson et al 2013. Challenges associated with primary isolation of SAV are also in accordance with our unpublished data from attempts to cultivate the virus from several outbreaks of PD in Norway.…”
supporting
confidence: 79%
“…Cohorts exposed to lower sea temperatures had significantly longer incubation periods than cohorts infected when the sea temperatures were higher (Stene et al 2014). Virus cultivation was unsuccessful, similar to earlier experiences with primary culture of SAV from infected fish (Christie et al 1998, López-Dóriga et al 2001, Graham et al 2003, Petterson et al 2013. Possible causes as low viral loads, virus neutralizing antibodies and/or defective virus particles in the samples have been suggested (Graham et al 2010, Petterson et al 2013.…”
Section: Discussionsupporting
confidence: 55%
“…In a previous study on the SAV3 subtype of SPDV, we documented that infectious virus (with full-length genome) is present alongside with numerous RNA deletion mutants in heart of clinically diseased Atlantic salmon, and we hypothesised that recombination of genomes was the explanation for this17. Using reverse genetics, we have shown that infectious virus can be rescued from cell lines transfected with full length SAV3 (FL-SAV3) plasmid18.…”
mentioning
confidence: 95%
“…pancreas disease (PD), heart and skeletal muscle inflammation (HSMI) and cardiomyopathy syndrome (CMS). Viral cause of the diseases, the salmonid alphavirus 3 (SAV3), piscine reovirus (PRV) and piscine myocarditis virus (PMCV), respectively, have been presented [20][23], but none of them have shown to be easy to cultivate in cell culture except for a few isolates of SAV3 causing PD [24], [25]. In an attempt to isolate a viral agent from heart samples from farmed Atlantic salmon with HSMI, we obtained a virus isolate not previously found in Atlantic salmon.…”
Section: Introductionmentioning
confidence: 99%